Variation in Plasma Calcium with Induced Changes in Plasma Specific Gravity, Total Protein, and Albumin. Issue 5893 (15th December 1973) - Berry, E. M.; Gupta, M. M.; Turner, S. J.; Burns, R. R.
Abstract : The relationship of plasma calcium levels to changes in plasma specific gravity, total protein, and albumin induced by venous stasis was investigated. Factors were derived for adjusting calcium results to offset the effects of variation in protein concentration and thus to make them of increased discriminatory value to the clinician. The validity of an existing specific gravity correction has been substantiated, but a more exact adjustment of 0·23 mg/100 ml of calcium for every 0·001 change in specific gravity is proposed. We recommend for automated laboratories that the factor based on albumin be used: 0·09 mg/100 ml of calcium should be subtracted from the total calcium value for every increase of 0·1 g in albumin above 4·6 g/100 ml, and a corresponding addition should be made for values of albumin below 4·6 g/100 ml. Using a calcium specific electrode, it has been shown that the ionized calcium concentration does not alter with prolonged venous stasis.